OS7.1 Impact of the addition of Rituximab to standard therapy with high dose methotrexate on health-related quality of life in primary central nervous system lymphoma patients. (6th September 2019) - van der Meulen, M; Dirven, L; Bakunina, K; Taphoorn, M J B; van den Bent, M J; Issa, S; Doorduijn, J K; Bromberg, J E C
Abstract: BACKGROUND: Data on the impact of treatment with Rituximab on health-related quality of life (HRQoL) in primary central nervous system lymphoma (PCNSL) patients are scarce. To determine the net clinical benefit of a new treatment, analyzing the effect on HRQoL is warranted. MATERIAL AND METHODS: Patients from a phase III trial (HOVON 105/ ALLG NHL 24), randomized to standard chemotherapy with or without Rituximab, were asked to fill in the EORTC QLQ-C30 and QLQ-BN20 questionnaires before and during treatment, and up to 2 years follow-up or progression. Five predetermined scales were selected for primary analyses: global health status (GH), role (RF) and social functioning (SF), fatigue (FA), and motor dysfunction (MD). A difference ≥10 points was defined as clinically relevant. Cross-sectional analyses were performed comparing changes in HRQoL scores from baseline between the two arms at 12 and 24 months after treatment. Effect of whole brain radiotherapy (WBRT) was analyzed in irradiated patients only. Differences in HRQoL over time between the treatment arms, i.e. the primary outcome, were assessed using linear mixed models (LMM). RESULTS: 175/199 patients completed at least one HRQoL questionnaire, and compliance was >60% at all evaluation points. Median age was 61 (IQR 55–66), 74% had a WHO performance score <2, and 38% received WBRT, similar to the total trial population. HRQoL scores on all five scales were significantly and to a clinically relevant extent improved at 12 and 24 months follow-up when compared to baseline in both arms (range: 11.6–42.4), except for FA and MD at 12 months (both -7.2). Differences in HRQoL changes from baseline to 12 and 24 months between the two arms were not statistically significant (range: 3.6–10.9). In the irradiated patients (n=52), HRQoL scores remained stable up to 24 months compared to shortly after WBRT for GH, SF, FA and MD (range -8.1 - 7.6). A clinically relevant and statically significant improvement was seen in RF for both arms at 12 and 24 months compared to 'after WBRT'(range: +16.7 - +22.2). After correction for multiple testing, LMM analyses showed no statistically significant and clinically relevant differences between the arms for any of the scales over time (range: -3.8 to +4.0). CONCLUSION: Treatment resulted in improved HRQoL, but the addition of Rituximab to standard chemotherapy did not further impact HRQoL over time. WBRT did not result in deterioration of HRQoL up to 2 years of follow-up.